Influence of library infrastructure in developing scientific production in teachers and researchers from Mexican universities - Murguía Jáquez, Laura Patricia; Tarango Ortiz, Javier; Romo González, José Refugio ROMO GONZÁLEZ; Ascencio Baca, Gerardo (Revista General de Información y Documentación, 2013)
The role of university libraries in education has been considered relevant, because this to their contributions to support the academic and scientific activities that occur in higher education institutions, both for knowledge transfer and generation, by various actors interacting in relation to information resources. This article, based on the integration of a simplified theoretical model analyzes the behavior they see teachers and researchers from 33 universities in Mexico participating in accreditation processes, on various scientific production indicators (evaluated in three broad areas: quality, production and innovation), the while studying at the library infrastructure available, such as: printed volumes available, subscriptions to print journals, subscriptions to databases, quantity of teachers as users, quantity of students as users and physical area in square meters. From the statistical analysis and data weighting, due to the disparity in the size of the participating universities, developed a series of correlations; same that led to the identification of those physical infrastructure indicators have influenced those of scientific production, inferring addition, patterns of use and access to information resources by teachers and researchers.
Keywords: Scientific production; Communication of science; Library infrastructure; Mexican universities; accredited academic libraries.